Electrochemical separation : from ions to proteins - Fritz, Pina Atalanta (Nanyang Technological University, 2020)
Separation process are at the heart of many industries ranging from chemical to medical and food. To create innovative products, first specific components need to be purified or fractionated from the source of origin. Generally, this requires a large amount of energy and chemicals; therefore, more sustainable processing options need to be designed. Within this thesis, we investigate electrochemical separation processes for ions and proteins. These processes bear great potential to reduce energy and solvent use compared to membrane or chromatographic techniques, since electric energy is directly used without further conversion, and fast and easy switching between e.g. negative and positive surfaces makes it unnecessary to regenerate solid supports with solvents or buffers. Nevertheless, to unfold the full potential of electrochemical separation processes, development of electrodes for selective separation, and the design of the overall process need to be taken to a next level. Both issues are crucial when extending the principles about ion separation to other molecules such as proteins that to date have been hardly explored in this context. We first review in Chapter 2 the current state of the art of electrochemical separation processes using capacitive or faradaic principles applied to small ions, proteins, and cells. An important point that is reviewed is the difference between capacitive deionization and inverted capacitive deionization. In the former process, ions are stored capacitively in the electric double layer when a constant electrode potential or current is applied. The release of the ions occurs when releasing the electric bias or by reversing it. In contrast during the latter process, ions are stored due to chemical surface charges and the additional electric potential is only applied during the regeneration phase. Since in this option selective surface coatings may be used, it allows for specifically targeting molecules within a mixture, and still operating without solvents for regeneration. This is a major advantage for protein separation, and thus used in the following chapters, starting from a system with salt that later becomes more complex by the introduction of protein. In Chapter 3 and 4 we investigate simple and modified activated carbon electrodes in an inverted capacitive deionization process. We found that ion adsorption at 0 V was possible for simple activated carbon electrodes when used with ion exchange membranes in front of the electrodes (inverted capacitive membrane deionization). We also found a similar separation pattern for electrodes with polyelectrolytes added to the matrix, which in combination with ion exchange membranes resulted in a process that is competitive with conventional capacitive deionization at very low exergy loss. When working with a solution that contains proteins, electrode fouling is a challenge. In Chapter 5 we show that the application of hierarchical carbon electrodes coated with a zwitterionic polymer brush avoids protein adsorption and increases the life time of the electrodes during desalination. However, when proteins need to be separated, they need to interact with the surface of the electrode while still desorbing upon an electric trigger. In Chapter 6 we show that activated carbon electrodes containing cationic and anionic polyelectrolytes have the ability to reversibly adsorb and release protein by applying an electric potential bias. While proteins were adsorbed, salt was desorbed and vice versa, therewith also showing a potential for desalting protein solutions. In Chapter 7 we investigated the forces acting on salt and proteins in detail, and measured an increase in electric and hydration repulsion at the electrode interface due to an externally applied electric potential which influenced surface wetting. Overall, we concluded that the changes induced by the electric potential were sufficient to influence protein ad- and desorption. Since in Chapter 7 the measurements were conducted on gold substrates, we presented in Chapter 8 as a first step toward carbon based electrodes reduced graphene oxide coated silicon substrates to study protein ad- and desorption. The findings described in this thesis are important for the development of novel electrochemical separation processes for complex molecules, and they lay the ground work for a next generation of sustainable separation technologies. Thus, in Chapter 9 our findings were put into perspective, and we highlighted research required to further design electrochemical separation processes. We indicated that suitable (responsive) surface coatings, and optimized process designs for large scale applications are key to unlock the full potential of electrochemical separation processes and to guarantee their successful implementation.